KKB kanya-kanyang bigay : UI/UX design for a food-sharing mobile application used to redistribute food and reduce food waste in Metro Manila - Utlang, Diana Mae R.; San Valentin, Marc (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
Food waste refers to discarding of food that have reached their final stage and are already products fit for consumption and is a global problem that concerns not only the negative impacts it causes to the environment, but also climate change, food security, and public health. Filipinos waste rice enough to feed 4.3 million Filipino people. Metro Manila alone wastes 2,175 tons of food per day. 2.7 million Filipino families still experience involuntary hunger at least once every three months (SWS, 2017). We could then infer that food availability is not the problem but accessibility. Since food waste happens on the consumption side such as in food establishments and in the household, it may be a product of human behavior. How do Filipino Food Culture and Eating Habits Affect Food Waste in Metro Manila? This study aims to study the Filipino culture and eating habits across different age groups and geographic areas; To determine a relationship between food consumption behaviors and food wastage; study the underlying problems of Filipino food culture and eating habits; and finally identify ways and recommend more sustainable food habits fit for Filipinos as a means to minimize food wastage. The researcher approached WWF Philippines as a key informant, as well as conducting two focus group discussions supplemented by in-depth interviews, to gather different insights on food consumption behavior and varying perceptions regarding food waste. From the data gathered and in respect to the study's objectives, the researcher concludes with these findings: Food waste is directly affected by an individual's culture and food habits; an individual's socio-economic background and geographic area determines ones culture and food habits; urbanization largely contributes to the increase of food waste in the Philippines; switching to a more sustainable food habit, despite its importance and benefits, demands effort. Encouraging the dining public to switch to a more sustainable food habit may prove to be challenging as it is a behavior that cannot be done by an individual alone out of awareness, but has to be enforced and carried out through outside factors surrounding the individual for them to follow suit; such as turning it into a social norm, providing a channel to transfer excess food to those who need it and making sustainable food options more available and accessible to them.
Thesis (Bachelor of Arts in Visual Communication)--University of the Philippines Diliman
Bibliography : leaves 172-173.
Keywords: Food waste -- Philippines; Food habits -- Philippines; Mobile apps